Penggunaan Aplikasi DW Learn German sebagai Penunjang Matakuliah B1-Prüfungsvorbereitung - Mochamad Rezkyansyah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2020)
This article aims to describe the use of the application DW Learn German to understand the information in the audio in the subject B1-Prüfungsvorbereitung in the German Literature Department, State University of Malang. The research method used is a descriptive method with data in form of a score of listening ability after using the application. Sources of research data were all students of year 2018 at offering B who took the course B1-Prüfungsvorbereitung. The results showed that students' listening skills increased after using the DW Learn German application. The DW Learn German application as a support for the course B1-Prüfungsvorbereitung can help improving students' listening skills, especially in understanding the essence of long texts. The texts that are used as question stimuli in the DW Learn German application are long texts with a duration of 1.5 minutes, approximately 250 words per text, in the context of daily activities with various topics.